An LP-based approach for loading and routing in a flexible assembly line - Sawik, Tadeusz (International journal of production economics, 2000)
The paper presents integer programming formulations and a heuristic solution procedure for a bicriterion loading and assembly plan selection problem in a flexible assembly line. The problem objective is to simultaneously determine an allocation of assembly tasks among the stations and select assembly sequences and assembly routes for a mix of products so as to balance station workloads and to minimize total transportation time in a unidirectional flow system. In the approach proposed, first the station workloads are balanced using a linear relaxation-based heuristic and then assembly sequences and assembly routes are selected for all products, based on a network flow model. An illustrative example is provided and some computational results are reported.